International Didactic Project Multilingualism of the Baltic Region: Institute of Specialised and Intercultural Communication, University of Warsaw - Małachowicz, Marta; Piotrowska, Joanna (Slavistica Vilnensis, 2022)
The announcement presents the conception of the didactic project Multilingualism of the Baltic region, which has been carried out since the second half of 2022 in the Institute of Specialised and Intercultural Communication at the University of Warsaw thanks to funding granted by the university’s Teaching Excellence Fund. Special attention is given to the first part of the project focused on the language situation in Lithuania. This part of the project has been already completed. In October 2022, professors from Vilnius University, Lithuania taught a specialist course held in Russian language consisting of seven seminars and practical training. These types of projects respond to demand expressed by students interested in exploring languages and cultures of the Baltic region. They also pursue the goals of a contemporary university aiming for innovation in teaching.